Pharmacological interventions for treating chronic prostatitis/chronic pelvic pain syndrome - Franco, Juan VA (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of pharmacological therapies for chronic prostatitis/chronic pelvic pain syndrome.